Assessment of intra-fractional and inter-fractional motion in esophageal cancer treated with intensity-modulated proton therapy - Xiaoying Fan; Shuting Wang; Weijie Li; Kangning Meng; Wei Huang; Yong Yin; Tianyuan Dai (BMC Cancer)
Abstract Propose Proton therapy of esophageal cancer is beneficial to spare normal tissue in clinical practice. However, intra-fractional and inter-fractional variance of tumor motion during treatment may compromise target coverage. The purpose of this study was to investigate the interplay effect due to intra-fractional motion and the effect of the robust optimization parameters for inter-fractional motion in the intensity modulation proton therapy (IMPT). Materials and methods This study retrospectively analyzed 42 patients with esophageal cancer treated at Shandong Cancer Hospital. The patients were divided into two groups. Twenty-one patients had a 4DCT image with 10 respiratory phases reconstructed (Gintra). In addition, twenty-one patients underwent a second 3D CT scan following the initial one (Ginter). The RayStation11B treatment planning system was used to create the IMPT plans for these two groups of patients. All patients were planned with a prescribed dose of 50.4 Gy (RBE) in 28 fractions for clinical target volume (CTV). 4D dynamic dose (4DDD) was then calculated to assess the interplay effect by considering respiratory motion and dynamic beam delivery for Gintra. Seven IMPT plans with different robust optimization parameters were designed for the 21 Ginter patient. The setup uncertainties were set to ± 0–6 mm for Ginter. Plan quality and dose-volume histogram (DVH) parameters for the target and organs at risk (OARs) were then analyzed. Results For Gintra, 4DDD was slightly perturbated compared to the nominal plan dose. The mean value of CTV D98% of nominal dose and 4DDD were 49.9 and 49.1 Gy (RBE), respectively, and the CTV D95% were 50.4 and 49.9 Gy (RBE), respectively. For Ginter, the DVH parameters of the target area and the OARs showed a linear relationship with the corresponding robust optimization parameters in IMPT. When the robust optimization parameters were set with a larger value, the dose coverage of the target was improved. However, the dose of OARs increased at the same time. The D98% of the target for the seven plans (setup6, setup5, setup4, setup3, setup2, setup1, setup0 plan) were 49.42 ± 0.75, 48.95 ± 1.21, 48.54 ± 1.48, 47.55 ± 2.31, 47.07 ± 2.71, 44.58 ± 4.20 and 44.02 ± 4.44 Gy(RBE), respectively. The Dmean of heart were 12.18 ± 3.05, 11.28 ± 2.86, 10.90 ± 2.77, 9.76 ± 2.39, 9.73 ± 2.39, 8.33 ± 2.22 and 8.22 ± 2.20 Gy (RBE), respectively. Conclusion In this study, the differences in dose distributions between the 4DDD and nominal plans for Gintra can be attributed to the interplay effects. While target coverage remained stable, variations in OAR doses should be evaluated for Gintra. For Ginter, smaller setup uncertainty parameters may not fully mitigate inter-fractional tumor motion, leading to greater variation in target dose and potential inadequate coverage. The linear relationship between setup uncertainty and D98% suggested that improved setup uncertainties can enhance target coverage, while higher setup uncertainties tend to increase OARs doses, particularly to the heart and lungs.